PENINGKATAN KETERAMPILAN TUKANG BAGI MASYARAKAT PROVINSI BANTEN MELALUI EDUKASI VOKASI PROGRAM KOTA TANPA KUMUH DI UNIVERSITAS BANTEN JAYA - Telly Rosdiyani; Fitri Aida Sari (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2021)
Banten Province consists of four districts and four cities, namely: Pandeglang Regency, Lebak Regency, Tangerang Regency, Serang Regency, Tangerang City, Cilegon City, Serang City, and South Tangerang City. With population growth data continues to increase It is KOTAKU Program conducting training activities in collaboration with universities Of Banten Jaya University. city without slums (Kotaku) program is one of the strategic efforts of the Directorate General of Copyright Works of the Ministry of Public Works and Public Housing target training for citizens who are oriented on improving skills, skills, knowledge, attitudes, work habits that drive towards improving the quality of infrastructure built and developing community sustainability Building builder training activities were carried out for 4 days on December 1 - 4, 2020 with a total of 30 participants with indoor and outdoor learning methods in practical materials. Implementation of K3 in work, foundation work, repair work, installation work, wood horse making work, as well as stucco work as training material. The results of the evaluation of the participants showed improvement in understanding the skills of the craftsmen but this skill must be coupled with continued training in the field so that the need for coaching and involved participants in other infrastructure projects